Social cues to joint actions: the role of shared goals - Sacheli, Lucia M.; Aglioti, Salvatore M.; Candidi, Matteo (Frontiers in Psychology, 2015)
In daily life, we do not just move independently from how others move. Rather, the way we move conveys information about our cognitive and affective attitudes towards our conspecifics. However, the implicit social substrate of our movements is not easy to capture and isolate given the complexity of human interactive behaviors. In this perspective article we discuss the crucial conditions for exploring the impact of “interpersonal” cognitive/emotional dimensions on the motor behavior of individuals interacting in realistic contexts. We argue that testing interactions requires one to build up naturalistic and yet controlled scenarios where participants reciprocally adapt their movements in order to achieve an overarching “shared goal”. We suggest that a shared goal is what singles out real interactions from situations where two or more individuals contingently but independently act next to each other, and that “interpersonal” socio-emotional dimensions might fail to affect co-agents’ behaviors if real interactions are not at place. We report the results of a novel joint-grasping task suitable for exploring how individual sub-goals (i.e. correctly grasping an object) relate to, and depend from, the representation of “shared goals”.